Impacts of Large Dams: A Global Assessment - Tortajada, Cecilia.; Tortajada, Cecilia.; Altinbilek, Dogan.; Altinbilek, Dogan.; Biswas, Asit K.; Biswas, Asit K. (Water Resources Development and Management, 2012)
One of the most controversial issues of the water sector in recent years has been the impacts of large dams. Proponents have claimed that such structures are essential to meet the increasing water demands of the world and that their overall societal benefits far outweight the costs. In contrast, the opponents claim that social and environmental costs of large dams far exceed their benefits, and that the era of construction of large dams is over. A major reason as to why there is no consensus on the overall benefits of large dams is because objective, authoritative and comprehensive evaluations of their impacts, especially ten or more years after their construction, are conspicuous by their absence. This book debates impartially, comprehensively and objectively, the positive and negative impacts of large dams based on facts, figures and authoritative analyses. These in-depth case studies are expected to promote a healthy and balanced debate on the needs, impacts and relevance of large dams, with case studies from Africa, Asia, Australia, Europe and Latin America.